The relationship between women’s empowerment and fatalism and self-care behaviors in COVID-19 virus - Mitra Savabi-Esfahani; Maryam Naji-Abhary; Fariba Taleghani; Mahnaz Noroozi; Mahdieh Saeri; Mahboobe Gholami; Zahra Mohebbi-Dehnavi (Journal of Education and Health Promotion)
BACKGROUND: Self-care and empowerment is one of the important aspects of a health-oriented lifestyle and the prevention of coronavirus outbreak. Considering the importance of women’s health and their very important role in creating a healthy society, the present study was conducted to determine the relationship between women’s empowerment and Fatalism with self-care behaviors about COVID-19 virus. MATERIALS AND METHODS: The present study is a descriptive study that was performed on 502 women referring to selected comprehensive health service centers in Isfahan (Nawab, Motahhari, Ibn Sina, 25 Dastgerd) in 2021. Women aged 18 to 45 years referring to the above centers who met the inclusion criteria completed women’s empowerment, self-belief, and self-care questionnaires. The collected data were analyzed by SPSS software version 22 and the Spearman test. RESULTS: The results of data analysis with the Spearman test showed that there is a significant negative relationship between the variable of Fatalism and self-care behaviors. The results also showed that there is a significant positive relationship between women’s empowerment and self-care behaviors (P ˂ 0.05). CONCLUSION: According to the results of the present study, empowerment of women as one of the effective members of the family and society and also paying attention to the beliefs of individuals can play a decisive role in improving self-care behaviors.